Nanotechnology and Early Human Development - Stefano Nobile; Lucio Nobile (Applied Sciences, 2020)
The application of nanotechnology, molecular biotechnologies, and nano-sciences for medical purposes has been termed nanomedicine, a promising growing area of medical research. The aim of this paper is to provide an overview of and discuss nanotechnology applications in the early epochs of life, from transplacental transfer to neonatal/pediatric conditions. Diagnostic and therapeutic applications, mainly related to the respiratory tract, the neurosensory system, and infections, are explored and discussed. Preclinical studies show promising results for a variety of conditions, including for the treatment of pregnancy complications and fetal, neonatal, and pediatric diseases. However, given the complexity of the functions and interactions between the placenta and the fetus, and the complex and incompletely understood determinants of tissue growth and differentiation during early life, there is a need for much more data to confirm the safety and efficacy of nanotechnology in this field.